Preparation method of high-strength and high-toughness wood based on salt bridge structure
Patent Information
- Application Number
- CN202611448496.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-17
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这类技术存在两个突出问题:其一,缺乏动态可逆键的能量耗散机制--树脂固化后形成的是永久性共价交联网络,虽然能够提供较高的强度和刚性,但这种“刚性交联”不具备可逆断裂与重组的能力,当木材受到冲击载荷时,永久交联网络无法通过牺牲键的断裂来耗散能量,其韧性提升主要依赖于物理致密化而非分子层面的能量耗散机制,相比之下,具有动态可逆键(如氢键、离子键、金属配位键等)的网络结构能够在外力作用下通过可逆键的优先断裂来吸收冲击能,从而更有效地同步提升强度和韧性;其二,环保性欠佳,传统的酚醛树脂、脲醛树脂等含有甲醛等有害物质,树脂浸渍法涉及有机溶剂的使用或合成树脂本身的不可降解性,此外,这类方法中改性剂主要填充于木材细胞腔内而非细胞壁内部,与木材基质的结合主要依靠物理填充而非化学键合,长期使用中易流失,耐久性不足
1、本发明通过构建胍基-羧基盐桥超分子交联网络,利用盐桥结构兼具高结合能与动态可逆性的特点,在木材受力时作为可逆牺牲键优先断裂以耗散冲击能量,外力解除后沿特定构型重新形成,从而实现了强度与韧性的协同增强。经测试,改性木材的冲击强度提升148.9%,弯曲模量提升221.3%,弯曲强度提升437.0%,拉伸强度提升166.6%,各项力学性能均获得突破性提升。
Smart Images

Figure CN123000996A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of wood functional improvement technology, specifically relating to a method for preparing high-strength and tough wood based on salt bridge structure. Background Technology
[0002] For a long time, regardless of whether it's heat treatment modification, acetylation modification, or chemical modification methods such as resin impregnation, while improving wood strength, these methods often lead to a decrease in toughness and increased brittleness. The toughness of wood mainly depends on the weak interfaces in its multi-scale hierarchical structure, including the middle layer, hemicellulose, and intermolecular hydrogen bonds. These weak interfaces can induce shear slip in the wood structural modules, increasing plastic deformation, causing stress blunting at crack tips and crack deflection, thereby improving toughness. However, traditional heat treatment and chemical modification both cause changes in the weak interface structure of wood, leading to a significant decrease in the toughness of the modified material. How to maintain or even improve toughness while increasing strength has always been a core challenge in the field of wood modification.
[0003] In recent years, to achieve simultaneous improvements in strength and toughness, researchers have proposed a strategy of "partial delignification + cell densification." This involves removing lignin and some hemicellulose from wood through alkaline chemical pretreatment, causing numerous hydrogen bonds to form between the remaining cellulose molecules. Subsequent densification treatment can significantly improve the mechanical properties of the wood. However, this method relies heavily on the removal of lignin, a natural binder in wood cell walls. Removing lignin alters the original natural chemical structure and cell wall composition of the wood, severely damaging its natural structure and aesthetic properties. Furthermore, the lignin removal process generates pollutants such as chlorine, causing environmental damage. For applications such as architectural decoration and high-end furniture, where the natural texture and solid wood feel of the wood must be preserved, this strengthening solution, which sacrifices the wood grain structure, has severely limited applicability and fails to meet the market's dual demand for both strength and the preservation of natural wood grain.
[0004] The combination of resin impregnation and compression densification is currently a feasible wood reinforcement method in industry. Common methods include impregnating wood with water-based acrylic resin, phenolic resin, furfuryl alcohol resin, etc., and then achieving cell densification through hot pressing. These methods can indeed significantly improve the mechanical strength and dimensional stability of wood. However, this type of technology has two prominent problems: First, it lacks a dynamic reversible bond energy dissipation mechanism. After the resin is cured, it forms a permanent covalent cross-linked network. Although it can provide high strength and rigidity, this "rigid cross-linking" does not have the ability to break and recombine reversibly. When wood is subjected to impact loads, the permanent cross-linked network cannot dissipate energy through the breaking of sacrificial bonds. Its toughness improvement mainly depends on physical densification rather than a molecular-level energy dissipation mechanism. In contrast, network structures with dynamic reversible bonds (such as hydrogen bonds, ionic bonds, and metal coordination bonds) can absorb impact energy under external force through the preferential breaking of reversible bonds, thereby more effectively improving strength and toughness simultaneously. Second, it is not environmentally friendly. Traditional phenolic resins, urea-formaldehyde resins, etc. contain harmful substances such as formaldehyde. The resin impregnation method involves the use of organic solvents or the non-degradability of the synthetic resin itself. In addition, in this type of method, the modifier mainly fills the wood cell cavity rather than the cell wall. The combination with the wood matrix mainly relies on physical filling rather than chemical bonding. It is easy to be lost during long-term use and has insufficient durability.
[0005] Hydrogen bonds are crucial interactions between cellulose molecular chains within wood, playing a key role in its mechanical properties. In recent years, researchers have attempted to modify wood using the dynamic and reversible nature of hydrogen bonds, for example, by partially delignifying the cellulose molecules to regulate the dynamic and reversible hydrogen bond network, achieving self-compacting reinforcement. However, as a non-covalent interaction, hydrogen bonds have low individual bond energies. This makes cross-linked networks built solely by hydrogen bonds prone to premature dissociation at cross-linking points under significant external forces, failing to provide sufficient mechanical strength. While increasing hydrogen bond density can compensate for this weakness, such strategies often require complex chemical treatments or expensive nanomaterials, and their effectiveness remains limited by the inherently weak nature of hydrogen bonds. Furthermore, hydrogen bonds are extremely sensitive to moisture; water molecules can form competitive hydrogen bonds with cellulose hydroxyl groups, leading to a significant decrease in the mechanical properties of wood in humid environments. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing high-strength and tough wood based on salt bridge structure, which addresses the shortcomings of the prior art. The guanidinyl-carboxyl salt bridge structure constructed by the present invention is a multi-point synergistic ionic bond and hydrogen bond coupling configuration. Its binding energy is much higher than that of a single hydrogen bond, which can provide stronger cross-linking strength while ensuring dynamic reversibility. Moreover, the salt bridge structure has a certain ionic stability and is much less sensitive to moisture than hydrogen bonds, and can still maintain good mechanical properties in humid environments.
[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a method for preparing high-strength and tough wood based on salt bridge structure, comprising the following steps: S1. Carboxymethylation treatment of wood: Wood is immersed in an alkaline agent solution containing chloroacetic acid for 2-12 hours under normal pressure or vacuum conditions. Then the entire system is placed in a water bath to carry out the carboxymethylation reaction to obtain carboxymethylated wood. S2, L-arginine impregnation treatment: The carboxymethylated wood obtained by S1 is impregnated in an aqueous solution of L-arginine for 3 to 24 hours under normal pressure, vacuum or pressure conditions. After being taken out, it is air-dried to a moisture content of 5% to 30% to obtain L-arginine impregnated wood. S3. Hot pressing: The L-arginine-impregnated wood obtained in S2 is subjected to hot pressing to obtain high-strength and tough wood based on salt bridge structure.
[0008] Preferably, the alkalizing agent in S1 is an aqueous ethanol solution containing sodium hydroxide, wherein the volume fraction of ethanol in the aqueous ethanol solution is 60%~80%, and the mass fraction of sodium hydroxide in the alkalizing agent is 1%~10%.
[0009] Preferably, the mass fraction of chloroacetic acid in the alkalizing agent solution containing chloroacetic acid in S1 is 1%~10%; the volume ratio of the alkalizing agent solution containing chloroacetic acid to the wood is (3~10):1.
[0010] Preferably, the carboxymethylation reaction in S1 is carried out at a temperature of 70°C to 90°C for 4 to 10 hours. After the carboxymethylation reaction is completed, the wood is taken out and washed with water until the pH value of the final washing solution is less than 7.5.
[0011] Preferably, the mass fraction of the L-arginine aqueous solution in S2 is 1%~20%; the volume ratio of the L-arginine aqueous solution to carboxymethylated wood is (3~10):1.
[0012] Preferably, the hot pressing temperature in S3 is 120℃~160℃, and the hot pressing time is 0.5h~3h.
[0013] The present invention also provides a high-strength and tough wood based on a salt bridge structure prepared by the above method.
[0014] Compared with the prior art, the present invention has the following significant technical effects: 1. This invention constructs a guanidinyl-carboxyl salt bridge supramolecular crosslinking network. Utilizing the high binding energy and dynamic reversibility of the salt bridge structure, these bridges preferentially break as reversible sacrificial bonds when the wood is subjected to stress, dissipating impact energy. After the external force is removed, they reform along a specific configuration, thus achieving a synergistic enhancement of strength and toughness. Testing showed that the modified wood exhibited a 148.9% increase in impact strength, a 221.3% increase in flexural modulus, a 437.0% increase in flexural strength, and a 166.6% increase in tensile strength, demonstrating breakthrough improvements in all mechanical properties.
[0015] 2. Compared with hydrogen bond-based wood modification strategies, the guanidinyl-carboxyl salt bridge constructed in this invention is a multi-point synergistic ionic-hydrogen bond coupling configuration with a specific bidentate spatial geometry, and its binding energy is much higher than that of a single hydrogen bond or a single ionic bond. This multi-point synergistic effect enables the crosslinked network to form an efficient and stable physical anchor within the wood cell wall, achieving significant reinforcement without the need for complex nanomaterial assistance or harsh chemical treatment conditions. Dynamic mechanical analysis (DMA) results show that the storage modulus and loss modulus of the modified wood of this invention are significantly higher than those of ordinary compressed wood and blank wood, indicating that the salt bridge crosslinked network has excellent energy storage and dissipation capabilities under dynamic loads.
[0016] 3. This invention uses L-arginine and chloroacetic acid as the main modifying agents. The raw materials are widely available and have good biocompatibility. Furthermore, the entire preparation process does not involve the large-scale use of toxic heavy metal catalysts or volatile organic solvents. Unlike toughening methods that sacrifice the natural wood grain structure (such as the lignin-derived template method), this invention significantly improves mechanical properties while fully preserving the natural texture and macrostructure of the wood, better meeting market demands. In addition, the process steps of this invention are simple, the equipment requirements are low, and it is easy to achieve large-scale production.
[0017] The present invention will now be described in further detail with reference to the accompanying drawings and embodiments. Attached Figure Description
[0018] Figure 1 These are scanning electron microscope (SEM) microstructure images of blank wood from Comparative Example 1, compressed wood from Comparative Example 2, and the tough wood prepared in Example 1.
[0019] Figure 2 The Fourier transform infrared (FT-IR) spectra of the blank wood of Comparative Example 1 and the tough wood of Example 1 are shown.
[0020] Figure 3 The X-ray photoelectron spectroscopy (XPS-N1s) high-resolution spectra of the blank wood of Comparative Example 1 and the tough wood of Example 1 are shown.
[0021] Figure 4These are mechanical property test diagrams of blank wood from Comparative Example 1, compressed wood from Comparative Example 2, and the tough wood prepared in Example 1.
[0022] Figure 5 The graphs show the dynamic mechanical properties (DMA) of the blank wood of Comparative Example 1, the compressed wood of Comparative Example 2, and the tough wood prepared in Example 1 under varying temperature conditions.
[0023] Figure 6 The graphs show the dynamic mechanical properties (DMA) of the blank wood of Comparative Example 1, the compressed wood of Comparative Example 2, and the tough wood prepared in Example 1 under variable frequency conditions. Detailed Implementation
[0024] The wood used in the following examples and comparative examples is linden.
[0025] Example 1
[0026] This embodiment describes a method for preparing high-strength and tough wood based on a salt bridge structure, including the following steps: S1. Carboxymethylation treatment of wood: Prepare an 80% (v / v) aqueous solution of ethanol, then add sodium hydroxide (NaOH) at a mass fraction of 5% to obtain an alkalizing agent; then dissolve chloroacetic acid in the alkalizing agent at a mass fraction of 5% to obtain an alkalizing agent solution containing chloroacetic acid.
[0027] The wood was impregnated in the alkalizing agent solution containing chloroacetic acid at a volume ratio of 8:1 to wood under vacuum for 2 hours. After impregnation, the entire system (including the alkalizing agent solution containing chloroacetic acid and the wood) was placed in a water bath for carboxymethylation reaction at a temperature of 80°C for 6 hours. The wood after the reaction was completed was taken out and washed with water until the pH of the washing solution was 7.3 during the final wash, thus obtaining carboxymethylated wood.
[0028] S2, L-arginine impregnation treatment: The carboxymethylated wood obtained from S1 was impregnated in a 10% L-arginine aqueous solution with a volume ratio of 3:1 between the impregnation solution and the wood. The impregnation was carried out under vacuum for 5 hours. After impregnation, the wood was removed and air-dried at room temperature with the moisture content controlled at 15% to obtain L-arginine-impregnated wood.
[0029] S3, Hot pressing: The L-arginine-impregnated wood obtained from S2 was subjected to hot-pressing treatment at a temperature of 130℃ for 1.5 hours. After hot-pressing, high-strength and tough wood based on the salt bridge structure was obtained.
[0030] Comparative Example 1 Blank wood.
[0031] Comparative Example 2 Compressed wood. The wood is directly hot-pressed at a temperature of 130℃ for 1.5 hours.
[0032] Figure 1 These are scanning electron microscope (SEM) images of the blank wood (Comparative Example 1), the compressed wood (Comparative Example 2), and the strong and tough wood prepared in Example 1. The blank wood shows numerous intact, hollow xylem vessels with obvious pores between cell walls, exhibiting a loose structure. The compressed wood, after simple compression treatment, shows cell wall deformation and some flattening of pores, but still retains many cracks and gaps between cell walls, indicating poor interfacial bonding. The strong and tough wood has a dense and uniform microstructure; the xylem vessel cavities are essentially compacted and closed, the cell walls are tightly adhered, with only a few fine cracks and no obvious large gaps. This demonstrates that the modification treatment of this invention not only achieves compaction and densification of wood pores but also improves cell wall interfacial bonding through intermolecular interactions, constructing a dense and continuous microstructure, providing a structural basis for the mechanical strengthening and toughening of wood.
[0033] Figure 2 The figures show the Fourier transform infrared (FT-IR) spectra of the blank wood from Comparative Example 1 and the tough wood from Example 1. As shown, the blank wood at 3349 cm⁻¹... -1 The characteristic peak of the hydroxyl (OH) stretching vibration appears at [value missing]; in the modified, tough wood, this characteristic peak red-shifts to 3327 cm⁻¹. -1 The peak position shifts towards lower wavenumbers, indicating that intermolecular hydrogen bonds have formed between the hydroxyl groups in the wood matrix and the modified components. These hydrogen bonds increase the OH bond length and decrease the vibrational frequency. Meanwhile, the strong and tough wood at 1589 cm⁻¹... -1 A new absorption peak appears at a certain point, which is attributed to the NH bending vibration, proving the formation of salt bridge hydrogen bonds in the system.
[0034] Figure 3 The images show the high-resolution X-ray photoelectron spectroscopy (XPS-N1s) spectra of the blank wood from Comparative Example 1 and the tough wood from Example 1. The blank wood shows almost no N1s signal, indicating that the original wood contains almost no nitrogen. In contrast, the tough wood exhibits a distinct N1s characteristic peak. After peak fitting of the spectra, -NH2, C=NH, C-NH-C, and C=NH2 can be observed. + Characteristic signals of nitrogen-containing functional groups, including -NH2 and C=NH2. + These are typical groups of salt-bridged hydrogen bonds. The above infrared spectroscopy and XPS characterization results corroborate each other, confirming that salt-bridged hydrogen bonds were successfully constructed in the modified wood system. This non-covalent interaction is an important molecular mechanism for achieving the strengthening and toughening of wood.
[0035] Figure 4The figures show the mechanical properties of the blank wood (Comparative Example 1), the compressed wood (Comparative Example 2), and the high-strength wood prepared in Example 1. The results show that, compared to the blank wood, the high-strength wood prepared in this example exhibits a 148.9% increase in impact strength, a 221.3% increase in flexural modulus, a 437.0% increase in flexural strength, and a 166.6% increase in tensile strength. This invention utilizes a multi-point synergistic salt bridge structure formed between the guanidinium group on the L-arginine molecule and the carboxyl group on the carboxymethylated wood. Specifically, multiple NH sites on the guanidinium group are coupled to the same carboxylate group via ionic and hydrogen bonds, constructing a supramolecular cross-linked unit with a specific bidentate spatial configuration. Its binding energy is far higher than that of a single hydrogen bond or a single ionic bond, while also possessing a clear spatial geometric orientation and reversible break-reformation capability. This salt bridge structure combines high binding energy with dynamic reversibility: when the wood is subjected to stress, the salt bridge, as a reversible sacrificial bond, preferentially breaks to dissipate impact energy, thereby improving toughness; after the external force is removed, the salt bridge can reform along a specific configuration, thus achieving a simultaneous improvement in strength and toughness.
[0036] Figure 5 The graphs show the dynamic mechanical properties (DMA) of the blank wood of Comparative Example 1, the compressed wood of Comparative Example 2, and the tough wood prepared in Example 1 under varying temperature conditions. Figure 6 The figures show the dynamic mechanical properties (DMA) of the blank wood of Comparative Example 1, the compressed wood of Comparative Example 2, and the tough wood prepared in Example 1 under variable frequency conditions. The results show that, regardless of whether the dynamic mechanical properties are variable temperature or variable frequency, the storage modulus and loss modulus of the tough wood prepared in this example are greater than those of ordinary compressed wood and blank wood.
[0037] Example 2
[0038] This embodiment describes a method for preparing high-strength and tough wood based on a salt bridge structure, including the following steps: S1. Carboxymethylation treatment of wood: Prepare an ethanol aqueous solution with a volume fraction of 70%, then add sodium hydroxide (NaOH) with a mass fraction controlled at 4% to obtain an alkalizing agent; then dissolve chloroacetic acid in the alkalizing agent with a mass fraction controlled at 6% to obtain an alkalizing agent solution containing chloroacetic acid.
[0039] The wood was impregnated in the alkalizing agent solution containing chloroacetic acid at a volume ratio of 6:1 to wood under vacuum for 5 hours. After impregnation, the entire system (including the alkalizing agent solution containing chloroacetic acid and the wood) was placed in a water bath for carboxymethylation reaction at a temperature of 70°C for 8 hours. The wood after the reaction was completed was taken out and washed with water until the pH of the washing solution was 7.3 during the final wash, thus obtaining carboxymethylated wood.
[0040] S2, L-arginine impregnation treatment: The carboxymethylated wood obtained from S1 was impregnated in an 8% (w / w) L-arginine aqueous solution with a volume ratio of 4:1 (w / w) of impregnation solution to wood. The impregnation was carried out under vacuum for 4 hours. After impregnation, the wood was removed and air-dried at room temperature with the moisture content controlled at 10% to obtain L-arginine-impregnated wood.
[0041] S3, Hot pressing: The L-arginine-impregnated wood obtained from S2 was subjected to hot-pressing treatment at a temperature of 140℃ for 1 hour. After hot-pressing, high-strength and tough wood based on the salt bridge structure was obtained.
[0042] Compared to blank wood, the high-strength and tough wood prepared in this embodiment has an impact strength increased by 130.2%, a bending modulus increased by 202.8%, a bending strength increased by 365.1%, and a tensile strength increased by 146.8%.
[0043] Example 3
[0044] This embodiment describes a method for preparing high-strength and tough wood based on a salt bridge structure, including the following steps: S1. Carboxymethylation treatment of wood: Prepare an ethanol aqueous solution with a volume fraction of 75%, then add sodium hydroxide (NaOH) with a mass fraction controlled at 6% to obtain an alkalizing agent; then dissolve chloroacetic acid in the alkalizing agent with a mass fraction controlled at 6% to obtain an alkalizing agent solution containing chloroacetic acid.
[0045] The wood was impregnated in the alkalizing agent solution containing chloroacetic acid at a volume ratio of 3:1 to wood under vacuum for 6 hours. After impregnation, the entire system (including the alkalizing agent solution containing chloroacetic acid and the wood) was placed in a water bath for carboxymethylation reaction at a temperature of 75°C for 6 hours. The wood after the reaction was completed was taken out and washed with water until the pH of the washing solution was 7.3 during the final wash, thus obtaining carboxymethylated wood.
[0046] S2, L-arginine impregnation treatment: The carboxymethylated wood obtained from S1 was impregnated in a 12% L-arginine aqueous solution with a volume ratio of 3:1 between the impregnation solution and the wood. The impregnation was carried out under vacuum for 3 hours. After impregnation, the wood was removed and air-dried at room temperature with a moisture content controlled at 14%, thus obtaining L-arginine-impregnated wood.
[0047] S3, Hot pressing: The L-arginine-impregnated wood obtained from S2 was subjected to hot-pressing treatment at a temperature of 135℃ for 1.5 hours. After hot-pressing, high-strength and tough wood based on the salt bridge structure was obtained.
[0048] Compared to blank wood, the high-strength and tough wood prepared in this embodiment has an impact strength increased by 141.2%, a bending modulus increased by 213.5%, a bending strength increased by 384.6%, and a tensile strength increased by 127.5%.
[0049] This invention introduces the salt bridge structure between guanidine and carboxyl groups into the field of wood mechanical modification for the first time. The constructed guanidine-carboxyl salt bridge structure is a multi-point synergistic ionic bond and hydrogen bond coupling configuration. Its binding energy is much higher than that of a single hydrogen bond, which can provide stronger cross-linking strength while ensuring dynamic reversibility. Moreover, the salt bridge structure has a certain ionic stability and is much less sensitive to moisture than hydrogen bonds, and can still maintain good mechanical properties in humid environments.
[0050] In addition to arginine, the modifiers in this invention can also be compounds containing guanidine groups, such as leonurine, metformin, and tetramethylguanidine. These substances can also form salt bridge structures with carboxymethylated wood.
[0051] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing high-strength and tough wood based on salt bridge structure, characterized in that, Includes the following steps: S1. Carboxymethylation treatment of wood: The wood is immersed in an alkaline solution containing chloroacetic acid for 2 to 12 hours, and then the entire system is placed in a water bath to carry out the carboxymethylation reaction to obtain carboxymethylated wood. S2, L-arginine impregnation treatment: The carboxymethylated wood obtained by S1 is impregnated in an aqueous solution of L-arginine for 3h~24h, and then air-dried until the moisture content is 5%~30% to obtain L-arginine impregnated wood. S3. Hot pressing: The L-arginine-impregnated wood obtained in S2 is subjected to hot pressing to obtain high-strength and tough wood based on salt bridge structure.
2. The method according to claim 1, characterized in that, The alkalizing agent mentioned in S1 is an aqueous solution of ethanol containing sodium hydroxide, wherein the volume fraction of ethanol in the aqueous solution is 60%~80%, and the mass fraction of sodium hydroxide in the alkalizing agent is 1%~10%.
3. The method according to claim 1, characterized in that, The mass fraction of chloroacetic acid in the alkalizing agent solution containing chloroacetic acid in S1 is 1%~10%; the volume ratio of the alkalizing agent solution containing chloroacetic acid to the wood is (3~10):
1.
4. The method according to claim 1, characterized in that, The carboxymethylation reaction described in S1 has a reaction temperature of 70℃~90℃ and a reaction time of 4h~10h.
5. The method according to claim 1, characterized in that, After the carboxymethylation reaction described in S1 is completed, the wood is removed and washed with water until the pH value of the final washing solution is less than 7.
5.
6. The method according to claim 1, characterized in that, The mass fraction of the L-arginine aqueous solution in S2 is 1%~20%.
7. The method according to claim 1, characterized in that, The volume ratio of the L-arginine aqueous solution to the carboxymethylated wood in S2 is (3~10):
1.
8. The method according to claim 1, characterized in that, The hot pressing temperature described in S3 is 120℃~160℃, and the hot pressing time is 0.5h~3h.
9. A high-strength and tough wood based on a salt bridge structure, characterized in that, Prepared by the method described in any one of claims 1-8.
